Effects of oils, lotions, hand sanitizers, and mehendi on fingerprints captured through digital fingerprint scanner - Vinita Kumari; Mukesh Kumar Thakar; Biswajit Mondal; Surender Kumar Pal (Egyptian Journal of Forensic Sciences, 2021)
Abstract Background In this modern era, advancement in technology is seen in every aspect of our life making it comparatively much easier. Likewise, in the field of fingerprinting, the digital scanners have replaced conventional methods of taking fingerprints, as it is accurate and less time-consuming. In daily life, people often apply oils, lotions, hand sanitizers, and occasionally mehendi on their hands. These cosmetic and daily use products affect the digital recording of fingerprints, thus making it difficult for forensic experts to identify the real offender in many cases. The purpose of the study was to check the effect of oils, lotions, hand sanitizers, and mehendi on the fingerprint pattern. Results The present study was undertaken by taking 2700 fingerprints from 30 individuals. These fingerprints were recorded with the help of the SecuGen Hamster IV fingerprint scanner under controlled environmental conditions. The examination and comparison of fingerprint patterns were done on the basis of visibility (clarity and intensity). The presence of cosmetic and daily use products affected the visibility of digitally captured fingerprints. Different products caused different effects based on their properties. Synthetic mehendi, alcohol-based hand sanitizer, greasy lotion, and viscous oil caused significant differences in the fingerprint images by degrading the fingerprint quality. The non-greasy lotion and non-alcohol-based hand sanitizer showed less effect, whereas non-viscous oil and natural mehendi caused a minimal effect on the quality of fingerprint images. Conclusion The application of cosmetic and daily use products added an additional layer on the fingers which is not present naturally. The additional layer caused alterations in the fingerprint pattern of an individual. So, digital fingerprints should be collected after proper washing of hands.